MULTIPLE PATH PARTICLE DOSIMETRY MODEL CONCEPT AND ITS APPLICATION TO DETERMINE RESPIRATORY TRACT HAZARDS IN THE 3D PRINTING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The Multiple Path Particle Dosimetry (MPPD) model is computer software that estimates and visualizes the deposition, clearance, and retention of particles in the respiratory tract systems of humans, rats, and other species. The mathematical model provides a broad spectrum of settings and input options. This research aims to explore the MPPD model concept and determine the deposition fraction (DF), clearance, and retained mass in the human respiratory tract (HRT) based on the geometric mean diameter (GMD) and mass concentration (MC) of particulate matter (PM) emitted during the 3D printing process. We used the real-time air sample data collected during the 8-hour working shift in the 3D printing office. Ultrafine PM deposits mainly in lungs (56%), fine PM mostly deposits in the upper respiratory tract (URT) (41%) and lungs (39%), but coarse PM mostly deposits in the URT (81%). The biggest DF in lower respiratory tract is ultrafine PM (487 μg), the smaller DF is coarse PM (185 μg) and the smallest DF is fine PM (123 μg). The biggest DF in lung for all PM - lower lobes (fine PM - 60%, ultrafine PM, coarse PM - 61%). In a model, where exposure was 5 hours a day, five days a week, during one month, followed by one year of post-exposure period, it was shown that retained mass in the tracheobronchial (TB) region was 1% for ultrafine and coarse PM each, 2% for fine PM, and 55% for all PM in the pulmonary region. The MPPD software is an easily accessible and valuable tool for assessing the impact of PM on the HRT. Particulate matter decreasing in diameter, tend to deposit mostly in the deeper levels of HRT. Tracheobronchial region clearance is more rapid than pulmonary region clearance. Potentially for persons using the 3D-printer regularly the worst health impact could be associated with smaller size of PM, due to tendency deposit mostly in pulmonary region where the clearance rate is slower.